A Scenario-Based Model for the Study of Collaboration in Construction - Garcia, Alejandro; Murguia, Danny (Pontificia Universidad Católica del Perú. Facultad de Arte y Diseño, 2021)
The construction sector has been widely criticized for its low productivity, fragmented structure, and adversarial relationships. To address these problems, some industry actors are adopting innovations such as lean construction, digital technologies, and collaborative contracts. However, these transformative innovations are underpinned by inter organizational collaboration within complex supply chain networks. Understanding collaboration in theory and practice is a difficult task. Therefore, this study aims to investigate factors influencing collaboration and develop a model for inter-organizational collaboration. To achieve this aim, first, a literature review on collaboration in construction was conducted. Second, qualitative data were collected via semi-structured interviews using the critical incident technique. Third, data were deductively and inductively analyzed using thematic nodes. Data showed that collaboration can be classified into four dimensions: trust, project uncertainty management, client’s operational capability, and business relationships. Finally, an empirical framework was constructed using the scenario technique. Client attributes and Supply Chain Capabilities were found to be the most influential and uncertain factors. Based on these, four collaboration scenarios were developed and assessed with illustrative implications derived from the empirical data. The scenario-based model would provide a further understanding of inter-organizational collaboration within supply chains and would aid Lean Construction practitioners to develop collaborative relationships.
Keywords: Collaboration; Supply chain management; Lean construction; relationships; Scenarios; https://purl.org/pe-repo/ocde/ford#2.01.01